Introduction: How Different Were the European Elections of 2014? - van der Brug, Wouter (2016)
This issue brings together papers that focus on the question of whether and in which ways the 2014 European Parliament elections were different from previous ones. This is important from the point of view of emerging scholarship on changes in the EU and from the point of view of the self-proclaimed ‘This time it’s different!’ slogan from the Parliament. The papers centre around three themes: 1) the role of the Spitzenkandidaten, 2) media and voters, and 3) electoral behaviour.